Soil liquefaction measurement and adjustment system on shaking table for seismic simulation - Abdul Karim, Mahmud; Aulia Sakinah, Dea; Nugroho Nuradryanto, Dimas; Setiowati, Sulis; Novita Wardhani, Rika; Salimah, A'isyah; Yelvi, Yelvi (Faculty of Engineering, Universitas Negeri Yogyakarta, 2024)
The liquefaction simulator tool uses a one-axis shaking table model to determine soil features and behaviour that indicate liquefaction. This helps in implementing measures to mitigate its effects. The research system incorporates a frequency regulation system to control the speed of the 3-phase motor and a measurement system that monitors various variables associated with liquefaction. The variables include displacement, rocking table motion, acceleration, vibration frequency, and pore water pressure. This study used LabVIEW for frequency adjustment, data acquisition, processing, and presentation. LabVIEW improved the observations' accuracy using the linear regression method and descriptive statistical analysis at the data processing stage. The error value for the frequency adjustment without load was 1.65%, which increased to 8.75% when a load was applied. This study achieved a displacement measurement accuracy of 99.03% and an average pore water pressure measurement accuracy of 95.69%. The measurement accuracy of the accelerometer and accelerometer vibration frequency reached 66.98%.